A toada de Chico da Silva: uma experiência em sala de aula - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
This article is the result of the research carried out in the Arts classes at the Nossa Senhora do Carmo School in Parintins/AM during 2022. From the proposed activity plan, the objective was to experience the Amazonian imaginary in the sounds and visualities of the acts of the composer Chico da Silva. Anchored in the researchers/authors COSTA (2017), COSTA (2021), LOUREIRO (2015), (SCHLICHTA and TAVARES (2013), SOUZA (2008), LOPES and ZILLES (2015), TIAGO (2008) and THIIOLLENT (1986) we had the contribution to establish the theoretical and qualitative methodological foundations of this research. As a result, the research provided creative experiences between music, visual arts and performance, favoring knowledge of Amazonian culture.
Keywords: Arte - Estudo e ensino; Arte na educação; Cultura popular - Parintins (AM); LINGUISTICA, LETRAS E ARTES; Chico da Silva; Toada; Arte-educação; Parintins/AM